2012
DOI: 10.1016/j.biomaterials.2012.02.047
|View full text |Cite
|
Sign up to set email alerts
|

Integration of basal topographic cues and apical shear stress in vascular endothelial cells

Abstract: In vivo, vascular endothelial cells (VECs) are anchored to the underlying stroma through a specialization of the extracellular matrix, the basement membrane (BM) which provides a variety of substratum associated biophysical cues that have been shown to regulate fundamental VEC behaviors. VEC function and homeostasis are also influenced by hemodynamic cues applied to their apical surface. How the combination of these biophysical cues impacts fundamental VEC behavior remains poorly studied. In the present study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(75 citation statements)
references
References 49 publications
3
72
0
Order By: Relevance
“…Among these, flow-mediated endothelial Wall Shear Stress (WSS) and substrate topography are known to play a critical role in the control of vascular permeability in vivo. Previous studies reported on the combined effect of substrate topography and flow either on single cell migration or on the morphology of confluent monolayers [21][22]. However, their combined contribution to wound healing, although likely to be important, has never been addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, flow-mediated endothelial Wall Shear Stress (WSS) and substrate topography are known to play a critical role in the control of vascular permeability in vivo. Previous studies reported on the combined effect of substrate topography and flow either on single cell migration or on the morphology of confluent monolayers [21][22]. However, their combined contribution to wound healing, although likely to be important, has never been addressed.…”
Section: Introductionmentioning
confidence: 99%
“…One example is the effect of oxygen gradient, which induces SMC migration and ECM remodeling that is important to achieve a functional blood vessel [132]. In this section, we will mostly focus on the mechanical conditions that blood vessels face, but many of the other factors have also been experimented with, and there is room for more in depth understanding of the effects of all of these different factors and their interplay, such as in the case of basal topographic features and shear stress combined effect on endothelial cells [133].…”
Section: Preconditioningmentioning
confidence: 99%
“…The modulation of cellular behavior and differentiation by soluble factors, 15,[36][37][38][39] surface chemistry, [40][41][42][43][44] and biophysical attributes of the extracellular microenvironment [45][46][47][48] has been well established. While, the majority of studies have investigated only one type of biophysical or chemical cue in isolation, a limited number have explored the interaction between multiple biophysical cues, 11,49 surface chemistry, 19,50 or soluble cytoactive factors. 15 Here we have demonstrated that the simultaneous presentation of substratum topographic cues and surfaceassociated biochemical cues potently modulated cellular behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular endothelial cells have been documented to integrate the simultaneous presentation of multiple biophysical cues (substratum topography and apical shear stress). 11 Importantly, biophysical cues have been demonstrated to also modulate the response of cells to soluble cytoactive factors 12 as well as to therapuetic agents. 13,14 Additionally, the soluble culture environment can alter the response of cells to biophysical cues.…”
Section: Introductionmentioning
confidence: 99%